International Doctoral and Master’s Students: What the Data Tell Us - Marconi, Gabriele (International Higher Education, 2016)
International experience is seen as an asset for researchers and top service professionals, and students are well aware of it: within the OECD, 11% of master’s students and 25% of doctoral students are international. International students at these levels tend to choose countries investing substantial resources on R&D in tertiary educational institutions. This offers these countries an opportunity to attract future workers with advanced training, particularly in science and technology: in Luxembourg, the Netherlands, New Zealand, Switzerland and the United States more than half of those enrolled in a doctoral program in science, engineering or agriculture are international students.”